2011
DOI: 10.1037/12314-000
|View full text |Cite
|
Sign up to set email alerts
|

Treating dementia in context: A step-by-step guide to working with individuals and families.

Abstract: Dementia is a life-altering diagnosis for patients and loved-ones alike. Th e progressive disease causes cognitive, emotional, and behavioral changes that can frustrate the eff orts of even the most dedicated caregivers. Given the uniquely personal nature of dementia symptoms, treatment can be a supremely challenging experience, even for seasoned health care professionals.In this book, authors Susan M. McCurry and Claudia Drossel present a clear and practical blueprint for psychologists, physicians, nurses, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
19

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 0 publications
0
5
0
19
Order By: Relevance
“…Broadly speaking, NCD is a clinical syndrome defined by the symptoms associated with neuropathological changes. Defining symptoms include multiple deficits in cognitive skills, a notable decline from previous skill levels, and a significant disruption of daily routines and common activities (McCurry & Drossel, 2011). These changes must be progressive and irreversible in nature in order to differentially rule out treatable conditions with an abrupt onset, such as serious injury, medical illness, medication side effects, or a vitamin deficiency.…”
Section: Dementia Types Symptoms and Terminological Changesmentioning
confidence: 99%
“…Broadly speaking, NCD is a clinical syndrome defined by the symptoms associated with neuropathological changes. Defining symptoms include multiple deficits in cognitive skills, a notable decline from previous skill levels, and a significant disruption of daily routines and common activities (McCurry & Drossel, 2011). These changes must be progressive and irreversible in nature in order to differentially rule out treatable conditions with an abrupt onset, such as serious injury, medical illness, medication side effects, or a vitamin deficiency.…”
Section: Dementia Types Symptoms and Terminological Changesmentioning
confidence: 99%
“…As a consequence, their own health is being neglected. (McCurry & Drussel, 2011;Wallerstedt & Andershed, 2013) The study on family caregivers who deal with AD showed 31% of adults experienced stress, anxiety, depression, and 53% of them were not able to spend time with friends and families (Bedini & Gladwell, 2014). Most of the family caregivers who experienced higher loads were women than men.…”
mentioning
confidence: 99%
“…The burden as a caregiver has a positive correlation with negative emotions that may occur. The negative emotion is one of the main components that may influence the family caregiver's quality of life (Yu, Wang, He, Liang & Zhou, 2015;McCurry & Drussel, 2011;Zawadzki, Mondon, Peru, Hommet & Constans, 2011).…”
mentioning
confidence: 99%
“…Estudos realizados sob a vertente teórica da análise do comportamento também têm demonstrado preocupação em investigar e intervir sobre os processos comportamentais de idosos com CCL ou DA. Os pesquisadores têm proposto intervenções em diferentes aspectos da aprendizagem, considerando técnicas e estratégias para reabilitar diferentes tipos de desempenhos de idosos com DA, estimulando a recuperação de déficits comportamentais e/ou controlando excessos comportamentais (e.g., Goyos, Rossit, Elias, Escobal, & Chereguini, 2009;McCurry & Drossel, 2011;Taveira, Taveira, & Caxieta, 2012) e verificando a manutenção e recuperação de relações simbólicas envolvidas na reabilitação da memória e da linguagem (Aggio & Domeniconi, 2012;Camara, Ducatti, & Schmidt, 2017;Ducatti & Schmidt, 2016;Haydu, & Morais, 2009;Souza, 2011;Steingrimsdottir & Arntzen, 2011). Neste sentido, McCurry e Drossel (2011) sugerem que a análise funcional seja utilizada como técnica para avaliar todos estes comportamentos e estabelecer planos de intervenção.…”
Section: Intervenções Em Linguagem Baseadas Na Análise Do Comportamentounclassified
“…Jean, Bergeron, Análise do Comportamento, por sua vez, tem longa tradição no desenvolvimento de procedimentos de ensino de diversos tipos de repertório, inclusive aqueles incluídos na literatura nas chamadas "funções cognitivas", incluindo aqui os repertórios verbais. As pesquisas sob esta orientação teórica enfatizam que os procedimentos de ensino devem ser utilizados no contexto das necessidades de cada paciente, avaliadas por meio da Análise Funcional, que é uma ferramenta eficiente, tanto para identificar as necessidades de intervenção e as variáveis de controle implicadas nessas necessidades, quanto para indicar as intervenções que podem produzir mudanças que melhorem a qualidade de vida dos idosos com DA e de seus cuidadores(McCurry & Drossel, 2011). Partindo desse pressuposto, talvez a questão mais importante em procedimentos de reabilitação de idosos com DA não seja a definição de protocolos rígidos, aplicáveis a todos os pacientes, mas sim o desenvolvimento de procedimentos de ensino com fortes evidências de eficácias, que possam ser utilizados pelos profissionais na formulação de programas individualizados para idosos com DA.Procedimentos de ensino, como o FO e o SR, têm demonstrado eficácia na recuperação dos déficits causados pela demência, contudo é importante ressaltar a necessidade de se ampliar a pesquisa no ensino de habilidades funcionais para idosos, aquelas necessárias para manutenção de sua independência e autonomia.…”
unclassified